2014
DOI: 10.1016/j.genhosppsych.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity and hyperalgesia in somatoform pain disorders

Abstract: Objective: In psychiatry, pain disorders not explained by structural lesions have been classified for decades as somatoform pain disorders, the underlying concept being somatization. In a parallel move, somatic medicine has defined an expanding group of similar pain disorders, known as functional pain syndromes. Functional pain syndromes are characterized by enhanced pain sensitivity. The aim of our study was to investigate the proportion of patients with somatoform pain disorders who also meet the criteria of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 29 publications
3
28
0
7
Order By: Relevance
“…For example, the analgesic effect of the opioid agonist remifentanil with a clinical dose can be completely reversed by a negative expectation, whereas the expectation of pain relief is an important component of placebo analgesia . Patients with somatoform pain disorders show enhanced pain sensitivity, and negative emotional context, such as sadness, increases pain sensitivity in somatoform pain disorders, thereby contributing to the psychopathology of this disorder . In line with previous studies, our results demonstrated that emotion was significantly associated with the pathogenesis of PSPD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, the analgesic effect of the opioid agonist remifentanil with a clinical dose can be completely reversed by a negative expectation, whereas the expectation of pain relief is an important component of placebo analgesia . Patients with somatoform pain disorders show enhanced pain sensitivity, and negative emotional context, such as sadness, increases pain sensitivity in somatoform pain disorders, thereby contributing to the psychopathology of this disorder . In line with previous studies, our results demonstrated that emotion was significantly associated with the pathogenesis of PSPD.…”
Section: Discussionsupporting
confidence: 90%
“…Pain in the limbs, waist, and chest has also been reported. The patients may also have emotional conflicts or psychosocial problems, such as increased depression and anxiety, impaired social functions, and decreased quality of life …”
Section: Introductionmentioning
confidence: 99%
“…Persistent somatoform pain disorder (PSPD) is defined as a type of mental disorder that cannot be explained by structural or somatic injury [ 1 ]. PSPD patients often suffer from persistent, severe and distressing pain without sufficient explanatory peripheral pathology, and thus it is believed to originate from emotional conflicts or psychosocial problems.…”
Section: Introductionmentioning
confidence: 99%
“…The use of this standardized pain provocation test has already been demonstrated in earlier studies. [ 12 13 ] The standardized and calibrated peg was clipped on the middle finger, ear lobes, and second toe of both body sides for 10 seconds each. The participant was asked to rate pain immediately after the end of the 10 seconds on a numeric rating scale from 0–10, where 0 signifies “no pain” and 10 “the worst pain imaginable.”…”
Section: Methodsmentioning
confidence: 99%